Perceived neighborhood safety and aesthetic quality are associated with cognitive change over time. (20th December 2022) - Hyun, Jinshil; Qin, Jiyue; Katz, Mindy J.; Derby, Carol A.; Wang, Cuiling; Sliwinski, Martin J.; Lipton, Richard B.
Abstract: Background: Identifying factors that contribute to cognitive decline is critical to the design of interventions to help older adults maintain independence. Although several studies have investigated associations between neighborhood characteristics and cognitive decline, these studies have not properly considered practice‐related cognitive gains (i.e., retest effects), which may hamper accurate estimation of aging‐related cognitive decline over time. This study examined whether subjective neighborhood characteristics were associated with longitudinal changes in processing speed, an early marker of cognitive aging and impairment, after accounting for retest effects. Method: The analysis sample includes 316 individuals enrolled in the Einstein Aging Study (mean age = 78; 67% females; 46% non‐Hispanic Whites, 40% non‐Hispanic Blacks). Neighborhood characteristics, including perceived neighborhood safety, aesthetic quality, and social cohesion, were measured at enrollment from self‐reports (range = 1 poor to 5 excellent). Processing speed was assessed using the brief, smartphone‐administered Symbol Search Test, and was completed 6 times per day for 16 days. The 16‐day protocol was repeated every year for three years. Double negative exponential models were used to estimate the relation of neighborhood characteristics to asymptotic performance (i.e., fastest response time) at baseline and asymptotic change (the rate in which asymptotic performance changes across years). Result: Results suggested that perceived neighborhood safety was associated with better (i.e., faster) baseline asymptotic performance after controlling for demographic information and individual‐ and neighborhood‐level socioeconomic status (Table 1). A one‐point increase in perceived safety was associated with a 115 millisecond faster asymptotic response time at baseline. Neighborhood safety and aesthetic quality were associated with greater decline in asymptotic response time: asymptotic response time decreased by 42 milliseconds (for safety) and 60 milliseconds (for aesthetic quality) per year for a one‐point increase in safety and aesthetic quality (Figure 1). Conclusion: Perceived neighborhood characteristics were associated with both baseline cognitive performance and rates of cognitive change for a three‐year period among community‐dwelling older adults. It is possible that a disordered neighborhood environment may act as a chronic stress leading to long‐term cognitive decline. Future studies need to examine psychosocial and behavioral mechanisms to identify targetable area for intervention.